TaZrC solid solution ceramic powder, C / C-TaZrC-SiC composite material and preparation method thereof

Through physical wet ball milling and carbon thermal reduction reaction, combined with polyethylene glycol and polyethyleneimine additives, high-density and high-purity Ta0.5Zr0.5C solid solution ceramic powder was prepared. Through the impregnation method and pioneer impregnation and cracking and density enhancement process, the problem of introducing ultra-high temperature ceramic components into C/C composite materials was solved, achieving efficient and low-cost composite preparation, and improving the mechanical and ablation resistance of the material.

CN117586039BActive Publication Date: 2025-03-11CENT SOUTH UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311549315.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-06
Filing Date
2023-11-20
Publication Date
2025-03-11
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

The existing solid solution ceramic powder preparation methods have problems such as high preparation temperature and many impurities, and it is difficult to introduce ultra-high temperature ceramic components into the C/C composite matrix, which easily damages the fiber structure.

Method used

Using physical wet ball milling and combined with carbon-heat reduction reaction, a Ta0.5Zr0.5C solid solution ceramic powder with high density and high purity was prepared by adding additives such as polyethylene glycol and polyethyleneimine, and introduced into the C/C composite material through the impregnation method. Combined with the pioneer impregnation and cracking and density enhancement process, C/C-Ta0.5Zr0.5C-SiC composite material was prepared.

Benefits of technology

The preparation temperature of solid solution ceramic powder is reduced, the impurity content is reduced, the solid phase content of the ceramic components and the overall performance of the material are improved, and the matrix material structure is protected from damage from high-temperature reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117586039B_ABST
    Figure CN117586039B_ABST
Patent Text Reader

Abstract

The present invention discloses a Ta 0.5 Zr 0.5 C solid solution ceramic powder, C / C‑Ta 0.5 Zr 0.5 C-SiC composite material and preparation method thereof; physical wet ball milling combined with carbon thermal reduction reaction was used to prepare a C-SiC composite material with a density of 10.52 g / cm 3 Ta 0.5 Z r0.5 C solid solution ceramic powder, Ta 0.5 Zr 0.5 Ta C solid solution ceramic powder ball milling 0.5 Zr 0.5 C solid solution ceramic fine powder is mixed with water and polyethyleneimine to obtain solid solution ceramic slurry, and the C / C composite porous green body is impregnated in the solid solution ceramic slurry. After drying, a carbon / ceramic matrix is ​​obtained, and then polycarbosilane is used as a ceramic precursor to densify the carbon / ceramic matrix by impregnation and cracking of the precursor, thereby obtaining C / C‑Ta with excellent mechanical properties and ablation resistance. 0.5 Zr 0.5 C‑SiC composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of ultra-high temperature ceramic-based composite materials, and specifically relates to a TaZrC (Ta 0.5 Zr 0.5 C) solid solution ceramic powder, C / C-TaZrC-SiC(C / C-Ta 0.5 Zr 0.5 C-SiC) composite material and preparation method thereof. Background Art

[0002] In the frontier field of aerospace science and technology research today, hypersonic vehicles have an extremely important strategic position. The operating speed of hypersonic vehicles can usually reach five times the speed of sound or more. Its nose cone, wing tip, throat liner and tail nozzle connected to the scramjet combustion chamber and other key hot parts usually need to withstand ultra-high temperatures of more than 2000℃ and thermal erosion. The commonly used material systems today are usually unable to adapt to such harsh working environments. In this context, the research and development of new ablation-resistant thermal protection composite materials that are resistant to high temperatures and erosion and have stable physical and chemical properties during service is becoming a new research hotspot at home and abroad.

[0003] The commonly used material systems are: refractory metals and their alloys, ultra-high temperature ceramics (UTHCs) and C / C composites. Compared with refractory metals and their alloys, which are expensive, dense and have poor oxidation resistance, ultra-high temperature ceramics, including carbides, borides, nitrides, etc. of transition refractory metals (Zr, Hf, Ta, etc.), usually have a melting point above 3000℃, high thermal conductivity and can maintain the stability of their physical and chemical properties under extreme environments. However, ultra-high temperature ceramics also have the disadvantages of intrinsic brittleness and low fracture toughness of ceramic materials. C / C composites have excellent properties such as high specific strength, large specific modulus, low density, high temperature resistance and friction resistance, but they can react with O2 in an environment above 400℃, and are also prone to react with H2O and CO2 in high temperature environments, thereby causing material damage. Therefore, using the high temperature stability characteristics of ultra-high temperature ceramics to modify the matrix of C / C composites can help to give full play to the original performance advantages of C / C composites and to make up for their poor high temperature performance to a certain extent.

[0004] The ultra-high temperature ceramic material TaC has a melting point of up to 3880°C and a small thermal expansion coefficient (6.61×10 -6 / K), density is 14.3g / cm 3 , which is relatively low compared to metals, and has a hardness of 19GPa, which can basically meet the general structural strength requirements. ZrC, which belongs to the same ultra-high temperature ceramic, has a melting point of 3540℃ and a thermal expansion coefficient of 6.82×10 -6 / K, density is 6.73g / cm3 , with a hardness of 35GPa. They both have thermal shock resistance and excellent high-temperature mechanical properties, and are often used in the field of thermal protection materials. Both have face-centered cubic crystal structures, with similar atomic radii, and in carbide ceramics, the vacancy formation energy of Ta (3.5eV) is smaller than the vacancy formation energy of Zr (8.8eV). Therefore, under certain reaction conditions, the two carbide ceramics can form a completely miscible solid solution ceramic Ta between ZrC and TaC ceramics in equal molar ratios. 0.5 Zr 0.5 C. Different from the dual-phase carbide ceramics obtained by simply mechanically mixing TaC and ZrC, the synergistic effect produced by the solid solution of TaC and ZrC makes the single-phase ultra-high temperature solid solution ceramics have a lower density, and can comprehensively exert the performance advantages of ZrC and TaC ultra-high temperature ceramics, so that the performance produces a "1+1>2" result, thereby compensating for the shortcomings of single-phase ultra-high temperature ceramics. 0.5 Zr 0.5 C has the highest elastic modulus and hardness in the Zr-Ta-C system, excellent high-temperature performance, and exhibits the advantage of an extremely high melting point in terms of ablation resistance. It has broad application prospects as a thermal protection material for equipment such as hypersonic aircraft.

[0005] The existing solid solution ceramic powder preparation methods are divided into physical methods and chemical methods. The chemical method usually has a complex process, high raw material cost, and low output. Due to the diffusion problem between the solid solution components in the powder preparation process, the physical method usually requires hot pressing at a high temperature above 2100°C, which has extremely high requirements for equipment and generates a large number of impurity components due to incomplete reactions. The preparation methods for introducing ultra-high temperature solid solution ceramic components into the C / C composite material system currently include sol-gel method, precursor impregnation pyrolysis method and chemical vapor deposition method in the laboratory stage. However, in the finished materials obtained by the above preparation methods, the solid phase content of the solid solution ceramics is low, and there are a large number of residual impurities in the reaction process. The solid solution reaction usually occurs in the C / C composite body, which causes great damage to the fiber structure of the matrix. Therefore, they are more commonly used in the preparation of surface coatings of C / C composite systems, and it is more difficult to modify the matrix. Summary of the invention

[0006] In view of the problems of high temperature and more impurities in the physical preparation of traditional solid solution ceramic powders, as well as the difficulty in introducing ultra-high temperature ceramic components into the C / C composite matrix and the easy damage to the fiber, the first object of the present invention is to provide a Ta 0.5 Zr 0.5 The present invention provides a method for preparing a C solid solution ceramic powder. 0.5 Zr 0.5The preparation method of C solid solution ceramic powder is simple to operate, requires a low temperature for preparation, does not require additional pressure, has a high ceramic yield, and has fewer impurities.

[0007] The second object of the present invention is to provide Ta prepared by the above preparation method 0.5 Zr 0.5 C solid solution ceramic powder.

[0008] The third object of the present invention is to provide a C / C-Ta 0.5 Zr 0.5 The preparation method of C-SiC composite material provided by the invention has simple process flow, low cost and low equipment requirement.

[0009] The fourth object of the present invention is to provide C / C-Ta prepared by the above preparation method 0.5 Zr 0.5 C-SiC composite material.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] The present invention is a Ta 0.5 Zr 0.5 The preparation method of C solid solution ceramic powder comprises the following steps: ZrO2 powder, Ta2O5 powder and carbon black powder are mixed to obtain a mixed powder, and then ethanol, polyethylene glycol and polyethyleneimine solution are added to the mixed powder to obtain a mixed solution, the mixed solution is ball-milled to obtain a ball-milled slurry, the ball-milled slurry is dried and pressed to obtain a ceramic body, and the ceramic body is calcined to obtain Ta 0.5 Zr 0.5 C solid solution ceramic powder.

[0012] The Ta provided by the present invention 0.5 Zr 0.5 The preparation method of C solid solution ceramic powder is as follows: after fully mixing the raw materials, ethanol, polyethylene glycol and polyethylene imine are added to the mixture to obtain ball milling slurry, and after drying, the mixture is pressed and calcined to obtain the powder. The inventors have found that the introduction of polyethylene glycol as a forming agent helps to make the ceramic oxide powder easier to form and compact when pressed, and also helps to shorten the diffusion path between the ceramic components during the solid solution of the mixed powder during the high-temperature calcination process, which can effectively reduce the reaction temperature. At the same time, polyethylene imine is used as a dispersant to promote the uniform dispersion of the powder in the solution, which is also conducive to shortening the diffusion path between the solid solution components, reducing the reaction temperature, and preventing the solid solution reaction from being insufficient due to uneven mixing, and premature phase separation, and generating single-phase ceramic impurities.

[0013] The present invention adopts physical wet ball milling combined with carbon thermal reduction reaction to prepare a particle with a density of 10.52 g / cm 3 Ta0.5 Zr 0.5 C solid solution ceramic powder, the prepared solid solution ceramic powder has high crystallinity and high purity.

[0014] In a preferred embodiment, the ZrO2 powder has a particle size of 0.5 to 1.5 μm, a purity of ≥ 99.90 wt.%, and a density of 5.85 g / cm 3 .

[0015] In a preferred embodiment, the particle size of the Ta2O5 powder is 0.5-1.5 μm, the purity is ≥99.90 wt.%, and the density is 8.2 g / cm 3 .

[0016] In a preferred embodiment, the carbon black powder has a particle size of 0.1 to 0.3 μm, a purity of ≥99.90 wt.%, and a density of 2.2 g / cm 3 .

[0017] The inventors have found that by controlling the particle size of each raw material powder within the above range, the dispersibility of each raw material in the final ball-milled slurry can be optimized, thereby obtaining the optimal sintering performance.

[0018] In a preferred embodiment, in the mixed powder, the molar ratio of ZrO2 powder:Ta2O5 powder:carbon black is 2:1:13-15.

[0019] In a preferred embodiment, in the mixed solution, the solid-liquid mass volume ratio of polyethylene glycol to mixed powder is 1g:4.8-6.3cm 3 .

[0020] The inventors have found that controlling the amount of polyethylene glycol added within the above range can make the ceramic green body easy to shape and dense during the subsequent pressing process, and to a certain extent prevent the problem of premature phase separation of the solid solution ceramic components during the calcination process and reduce the sintering temperature. If the amount of polyethylene glycol added is too small, the pressed green body may not be well formed and dense, and will be in a loose powder state. In this state, it is easy to prematurely separate when sintered at the same temperature and cannot form a single-phase solid solution.

[0021] In a preferred embodiment, in the mixed solution, the mass ratio of ethanol to polyethylene glycol is 5 to 7:1.

[0022] In a preferred embodiment, in the polyethyleneimine solution, the mass concentration of polyethyleneimine is 10% to 20%, and the average molecular weight is 10,000 to 20,000.

[0023] In the actual operation process, deionized water is used to prepare the polyethyleneimine solution.

[0024] In a preferred embodiment, the mass ratio of the polyethyleneimine solution to the mixed powder is 1:6.3-7.3.

[0025] The inventors have found that controlling the mass ratio of polyethyleneimine solution to mixed powder within the above range can optimize the dispersibility of the mixed powder, prevent premature phase separation of solid solution ceramic components during calcination to a certain extent, and help reduce the sintering temperature.

[0026] In a preferred embodiment, the mixed solution is ball-milled to obtain ball-milled slurry, the rotation speed of the ball mill is 140 to 160 r / min, and the ball milling time is 6 to 9 hours.

[0027] In a preferred embodiment, the ball-milled slurry is dried at 80-100° C. for 24-36 hours to obtain a mixed material.

[0028] In a preferred embodiment, the calcination temperature is 1900-2000° C., the holding time is 1-3 hours, and the heating rate is 10-15° C. / min.

[0029] The present invention also provides Ta prepared by the above preparation method 0.5 Zr 0.5 C solid solution ceramic powder.

[0030] The Ta prepared by the present invention 0.5 Zr 0.5 The density of C solid solution ceramic powder is 10.52g / cm 3 , the obtained Ta 0.5 Zr 0.5 C solid solution ceramic powder has high crystallinity and high purity.

[0031] The present invention discloses a C / C-Ta 0.5 Zr 0.5 Preparation method of C-SiC composite material, Ta 0.5 Zr 0.5 Ta C solid solution ceramic powder ball milling 0.5 Zr 0.5 C solid solution ceramic fine powder, Ta 0.5 Zr 0.5 C solid solution ceramic fine powder, water and polyethyleneimine solution are mixed to obtain solid solution ceramic slurry, and the C / C composite porous body is impregnated in the solid solution ceramic slurry. After drying, a carbon / ceramic matrix is ​​obtained, and then polycarbosilane is used as a ceramic precursor to densify the carbon / ceramic matrix by impregnation and cracking of the precursor to obtain C / C-Ta 0.5 Zr 0.5 C-SiC composite material.

[0032] In the present invention, Ta is directly impregnated by impregnation. 0.5 Zr 0.5The C solid solution ceramic powder is introduced into the C / C composite porous body, and the slurry impregnation process does not involve high temperature reaction, which protects the matrix material and structure from damage to the greatest extent, and helps to improve the overall performance of the material. In the present invention, the stability, wettability and viscosity of the ceramic slurry are effectively improved by the polyethyleneimine dispersant, so that the ceramic slurry can fully impregnate the C / C composite porous body and increase the solid phase content of the ceramic component in the matrix modification process.

[0033] During the experimental exploration, the inventors tried a large number of dispersants, and only polyethyleneimine was the best dispersant, which made Ta 0.5 Zr 0.5 C solid solution ceramic powder was successfully introduced into the C / C composite porous body by impregnation method.

[0034] The preferred solution is to 0.5 Zr 0.5 C solid solution ceramic powder was ball milled at a speed of 260-280 r / min for 6-9 h to obtain Ta 0.5 Zr 0.5 C solid solution ceramic fine powder, the Ta 0.5 Zr 0.5 The particle size of the C solid solution ceramic fine powder is 0.3 to 0.8 μm.

[0035] The inventors found that through the above ball milling process, Ta with uniform particle size and narrow distribution and a particle size of 0.3 to 0.8 μm can be obtained. 0.5 Zr 0.5 C solid solution ceramic fine powder, and Ta 0.5 Zr 0.5 When the particle size of the C solid solution ceramic fine powder is within the above range, the powder in the slurry can be fully dispersed, the stability of the slurry is optimal, the viscosity is lowest, and an ideal solid content is obtained, thereby optimizing the performance of the final composite material. If the particle size is too small, the agglomeration effect of the nano-sized powder will affect the dispersibility of the ceramic powder in the slurry to a certain extent, thereby affecting the stability of the slurry, resulting in excessive slurry viscosity, and affecting the final impregnation effect.

[0036] In a preferred embodiment, in the solid solution ceramic slurry, Ta 0.5 Zr 0.5 The volume fraction of the C solid solution ceramic fine powder is 10% to 20%.

[0037] The inventor discovered that 0.5 Zr 0.5 When the volume fraction of C solid solution ceramic fine powder is controlled within the above range, it can be well introduced into the C / C composite porous green body by impregnation. If the solid phase content is too low, the performance improvement of the product is limited, while if it is too high, it is not conducive to the penetration of the green body and will also affect the performance of the composite material.

[0038] In a preferred embodiment, in the polyethyleneimine solution, the mass concentration of polyethyleneimine is 10% to 20%, and the average molecular weight is 10,000 to 20,000.

[0039] In the actual operation process, deionized water is used to prepare the polyethyleneimine solution.

[0040] In a preferred embodiment, the amount of polyethyleneimine solution added is Ta 0.5 Zr 0.5 C solid solution ceramic fine powder mass 0.4% ~ 0.8%.

[0041] In a preferred embodiment, the mixing method is ball milling, the rotation speed of the ball mill is 160 to 180 r / min, and the ball milling time is 1 to 3 hours.

[0042] Through the above ball milling process, the components can be fully mixed in the slurry, and the dispersant can be better combined with the powder.

[0043] In a preferred embodiment, the C / C composite porous body is obtained by densifying a carbon fiber preform by chemical vapor deposition, wherein the carbon fiber preform is a polyacrylonitrile carbon fiber 2.5D needle-punched structure, and the density of the carbon fiber preform is 0.4-0.5 g / cm 3 The density of the C / C composite porous body is 0.7-0.8 g / cm 3 , the porosity is 50% to 58%.

[0044] In a preferred embodiment, the C / C composite porous body is immersed in a solid solution ceramic slurry, and dried at 80 to 100° C. for 24 to 36 hours to obtain a carbon / ceramic matrix.

[0045] The preferred scheme is that the process of densification of carbon / ceramic matrix by precursor impregnation cracking is as follows: the carbon / ceramic matrix is ​​impregnated in the precursor solution, dried after impregnation, and cracked after drying, and the impregnation-cracking is repeated 10 to 14 times to obtain C / C-Ta 0.5 Zr 0.5 C-SiC composite material; the precursor solution consists of polycarbosilane and n-hexane, the mass ratio of polycarbosilane to n-hexane is 1:1-3; the cracking temperature is 1400-1600°C, the insulation time is 1-3h, and the heating rate is 10-15°C / min.

[0046] In the present invention, the average molecular weight of the polycarbosilane used is 1400-2000, and the ceramic yield is 50%-60%.

[0047] The present invention also provides C / C-Ta prepared by the above preparation method 0.5 Zr 0.5C-SiC composite material.

[0048] Compared with the prior art, the advantages of the present invention are:

[0049] (1) C / C-Ta prepared by the present invention 0.5 Zr 0.5 C-SiC composite materials introduce ultra-high temperature solid solution ceramic components into the C / C composite material matrix. The material is dense and has a low porosity, which gives play to the synergistic effect of ultra-high temperature ceramics. Compared with traditional single ceramic component composites such as C / C-SiC, C / C-ZrC-SiC, C / C-TaC-SiC, etc., it has better comprehensive performance in mechanical properties and ablation resistance.

[0050] (2) The present invention adopts physical wet ball milling combined with carbon thermal reduction reaction to prepare a particle with a density of 10.52 g / cm 3 Ta 0.5 Zr 0.5 C solid solution ceramic powder. Compared with the traditional process, the temperature conditions required for preparing solid solution ceramic powder are greatly reduced, and because it is prepared under pressureless conditions, the manufacturing cost and equipment requirements are greatly reduced. The prepared solid solution ceramic powder has high crystallinity and high purity.

[0051] (3) The present invention uses a slurry impregnation process to introduce Ta 0.5 Zr 0.5 The C solid solution ceramic component modifies the matrix of the C / C composite material. Compared with the traditional process, the solid phase content of the solid solution ceramic in the matrix material is greatly improved, which is more conducive to exerting the performance advantages of the solid solution ceramic component. In addition, since the slurry impregnation process does not involve high temperature reaction, the matrix material and structure are protected from damage to the greatest extent, which helps to improve the overall performance of the material.

[0052] (4) The present invention combines the precursor impregnation process to fill the pore problem that may exist in the slurry impregnation process, making the matrix material more compact and further improving the overall performance of the material.

[0053] In summary, the process flow of the present invention is simple, the cost of raw materials is low, the requirements for equipment are low, and the prepared composite material, the solid solution ceramic has a high solid phase content, the matrix structure and performance protection are better, the porosity is small, the density is high, the comprehensive performance is excellent, and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 is Ta provided in Example 1 0.5 Zr 0.5 XRD pattern of C solid solution ceramic powder.

[0055] Figure 2 is Ta provided in Example 1 0.5 Zr 0.5 SEM image of C solid solution ceramic fine powder.

[0056] Figure 3 is C / C-Ta in Example 1 0.5 Zr 0.5 C SEM image of the cross section of carbon / ceramic matrix.

[0057] Figure 4 is Ta obtained in Comparative Example 1 0.5 Zr 0.5 XRD pattern of C solid solution ceramic powder.

[0058] Figure 5 is Ta obtained in Comparative Example 1 0.5 Zr 0.5 XRD local enlarged image of C solid solution ceramic powder. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the illustrations and specific examples in the specification, but the protection scope of the present invention is not limited thereby.

[0060] Example 1

[0061] C / C-Ta 0.5 Zr 0.5 The weight of each component of the raw material for preparing the C-SiC composite material: ZrO2 powder 18.12g, Ta2O5 powder 32.50g, carbon black 11.47g, ethanol 28.95g, polyethylene glycol 5.79g, polyethyleneimine 12.2g, polycarbosilane 60g, and n-hexane 60g.

[0062] Preparation process:

[0063] (1) Solution preparation: 18.12 g of ZrO2 powder, 32.50 g of Ta2O5 powder and 11.70 g of carbon black powder were weighed according to the molar ratio of ZrO2:Ta2O5:carbon black=2:1:13.26, and the mixed powder was added to 28.95 g of ethanol solution according to the mass of polyethylene glycol:total volume of mixed powder=1:4.8 and the mass ratio of ethanol:polyethylene glycol=5:1. Then, 5.79 g of polyethylene glycol forming agent was added. According to the mass ratio of polyethylene imine:mixed powder=1:6.3, 9 g of polyethylene imine dispersant was added. After stirring, a mixed solution was obtained.

[0064] (2) Wet ball milling: Add the mixed solution obtained in step (1) into a nylon ball mill and mill the mixture at a rotation speed of 140 r / min for 6 h. Place the solution after ball milling in an oven at 80°C for 24 h, and then press the dried mixed powder solid with a hydraulic press to obtain a prefabricated mixed powder.

[0065] (3) High temperature calcination: The prefabricated mixed powder obtained in step (2) is placed in a vacuum sintering furnace, and the temperature is uniformly increased to 1900°C at a rate of 10°C / min in a vacuum environment below 2.0 Pa, and the temperature is kept for 1 hour, and then cooled to room temperature with the furnace. The solid solution ceramic powder is obtained, and then ball milled at 260r / min for 6 hours to obtain Ta 0.5 Zr 0.5 C solid solution ceramic fine powder.

[0066] (4) Slurry impregnation: Prepare a solid solution ceramic slurry with a solid content of 20%. Take 40 g of the Ta prepared in step (3) 0.5 Zr 0.5 C solid solution ceramic fine powder, add 14.88g of ionized water, according to Ta 0.5 Zr 0.5 3.2 g of polyethyleneimine was added to 0.8% of the mass of C solid solution ceramic fine powder, stirred evenly, and ball milled at a speed of 160 r / min for 1 h to obtain solid solution ceramic slurry. The solid solution ceramic slurry was fully impregnated into the C / C composite porous body, and then placed in an 80°C oven to dry for 24 h to obtain C / C-Ta 0.5 Zr 0.5 C carbon / ceramic matrix.

[0067] (5) Precursor impregnation cracking and densification: A precursor solution is prepared according to a mass ratio of polycarbosilane: n-hexane = 1:1, and the C / C-Ta obtained in step (4) is fully impregnated in a high-pressure reactor at room temperature. 0.5 Zr 0.5 After drying, the C substrate was placed in a vacuum sintering furnace in a vacuum environment below 2.0 Pa and heated to 1400°C at a rate of 10°C / min for 1 hour. The above process was repeated 10 times to obtain a dense C / C-Ta 0.5 Zr 0.5 C-SiC composite material.

[0068] The Ta obtained in this example 0.5 Zr 0.5 C solid solution ceramic powder Figure 1 As shown in the XRD diagram, the diffraction peak is between the TaC and ZrC peaks, with a certain offset relative to the two phase peaks, and there are no other miscellaneous peaks, indicating that a relatively pure Ta 0.5 Zr 0.5C solid solution, and the diffraction peak intensity is high and narrow, indicating a high degree of crystallinity. 0.5 Zr 0.5 SEM images of C solid solution ceramic fine powder are shown in Figure 2 As shown, the powder is nearly spherical, without obvious agglomeration, with a particle size of about 500 nm, a narrow particle size distribution, and good uniformity, which is conducive to the subsequent slurry impregnation process. 0.5 Zr 0.5 The SEM image of the cross section of the C composite material is shown in Figure 3 As shown, the black phase is C / C matrix and the white phase is Ta 0.5 Zr 0.5 C ceramics, Ta 0.5 Zr 0.5 C is more evenly distributed among the pores of the C / C matrix, indicating that the solid solution ceramic impregnation effect on the C / C matrix is ​​better.

[0069] The C / C-Ta obtained in this example 0.5 Zr 0.5 The mechanical properties of C-SiC composite materials were tested by three-point bending and single-edge notched beam bending tests. The test results showed that its flexural strength was 194.04MPa and its fracture toughness was 13.77MPa·m 1 / 2 The flexural strength of the composite material is increased by 31.33% compared with that of the C / C composite material. 6 W / m 2 Under high heat flux density oxyacetylene flame ablation conditions, the test showed that the mass ablation rate in 120s was 1.95mg / s and the line ablation rate was 7.98μm / s.

[0070] Example 2

[0071] C / C-Ta 0.5 Zr 0.5 The weight of each component of the raw material for preparing the C-SiC composite material: ZrO2 powder 18.12g, Ta2O5 powder 32.50g, carbon black 12.15g, ethanol 30.60g, polyethylene glycol 5.10g, polyethyleneimine 9.84g, polycarbosilane 60g, and n-hexane 60g.

[0072] Preparation process:

[0073] (1) Solution preparation: 18.12 g of ZrO2 powder, 32.50 g of Ta2O5 powder and 12.15 g of carbon black powder were weighed according to the molar ratio of ZrO2:Ta2O5:carbon black=2:1:13.77, and the mixed powder was added to 30.60 g of ethanol solution according to the mass of polyethylene glycol:total volume of mixed powder=1:5.55 and the mass ratio of ethanol:polyethylene glycol=6:1. Then, 5.10 g of polyethylene glycol forming agent was added. According to the mass ratio of polyethylene imine:mixed powder=1:6.8, 7.44 g of polyethylene imine dispersant was added. After stirring, a mixed solution was obtained.

[0074] (2) Wet ball milling: Add the mixed solution obtained in step (1) into a nylon ball milling jar and mill the mixture at a rotation speed of 150 r / min for 7.5 h. Place the solution after ball milling in a 90°C oven for drying for 36 h. After grinding, the dried mixed powder solid is compacted using a hydraulic press to obtain a prefabricated mixed powder.

[0075] (3) High temperature calcination: The prefabricated mixed powder obtained in step (2) is placed in a vacuum sintering furnace, and the temperature is uniformly increased to 1950°C at a rate of 12°C / min in a vacuum environment below 2.0 Pa, and the temperature is kept at this temperature for 2 hours, and then the mixture is cooled to room temperature to obtain Ta 0.5 Zr 0.5 C solid solution ceramic powder. After ball milling at 270r / min for 7.5h, Ta 0.5 Zr 0.5 C solid solution ceramic fine powder.

[0076] (4) Slurry impregnation: Prepare a solid solution ceramic slurry with a solid content of 15%. Take 40 g of the Ta prepared in step (3) 0.5 Zr 0.5 C solid solution ceramic fine powder, add 21.29g ionized water, according to Ta 0.5 Zr 0.5 0.6% of the mass of C solid solution ceramic fine powder was added with 2.40g polyethyleneimine, stirred evenly, and ball milled at a speed of 170r / min for 2h to obtain solid solution ceramic slurry. The solid solution ceramic slurry was fully impregnated into the C / C composite porous body, and then placed in a 90℃ oven to dry for 36h to obtain C / C-Ta 0.5 Zr 0.5 C carbon / ceramic matrix.

[0077] (5) Precursor impregnation cracking and densification: A precursor solution is prepared according to a mass ratio of polycarbosilane: n-hexane = 1:2, and the C / C-Ta obtained in step (4) is fully impregnated in a high-pressure reactor at room temperature. 0.5 Zr 0.5After drying, the C substrate was placed in a vacuum sintering furnace in a vacuum environment below 2.0 Pa and heated to 1500°C at a rate of 12°C / min for 2 hours. The above process was repeated 12 times to obtain a dense C / C-Ta 0.5 Zr 0.5 C-SiC composite material.

[0078] The C / C-Ta obtained in this example 0.5 Zr 0.5 The mechanical properties of C-SiC composite materials were tested by three-point bending and single-edge notched beam bending tests. The test results showed that its flexural strength was 180.52MPa and its fracture toughness was 11.98MPa·m 1 / 2 The flexural strength is increased by 20.35% compared with C / C composite materials. 6 W / m 2 Under high heat flux density oxyacetylene flame ablation conditions, the test showed that the mass ablation rate in 120s was 2.02mg / s and the line ablation rate was 7.86μm / s.

[0079] Example 3

[0080] C / C-Ta 0.5 Zr 0.5 The weight of each component of the raw material for preparing the C-SiC composite material: ZrO2 powder 18.12g, Ta2O5 powder 32.50g, carbon black 12.15g, ethanol 30.60g, polyethylene glycol 5.10g, polyethyleneimine 9.84g, polycarbosilane 60g, and n-hexane 60g.

[0081] Preparation process:

[0082] (1) Solution preparation: 18.12 g of ZrO2 powder, 32.50 g of Ta2O5 powder and 12.60 g of carbon black powder were weighed according to the molar ratio of ZrO2:Ta2O5:carbon black=2:1:14.28, and the mixed powder was added to 31.99 g of ethanol solution according to the mass of polyethylene glycol:total volume of mixed powder=1:6.3 and the mass ratio of ethanol:polyethylene glycol=7:1. Then 4.57 g of polyethylene glycol forming agent was added. According to the mass ratio of polyethylene imine:mixed powder=1:7.2, 8.78 g of polyethylene imine dispersant was added. After stirring, a mixed solution was obtained.

[0083] (2) Wet ball milling: Add the mixed solution obtained in step (1) into a nylon ball mill and mill the mixture at a rotation speed of 160 r / min for 9 hours in a planetary ball mill. Place the solution after ball milling in an oven at 100°C for 48 hours, and then press the dried mixed powder solid with a hydraulic press after grinding to obtain a prefabricated mixed powder.

[0084] (3) High-temperature calcination: The prefabricated mixed powder obtained in step (2) is placed in a vacuum sintering furnace, and the temperature is uniformly increased to 2000°C at a rate of 15°C / min in a vacuum environment below 2.0 Pa, and the temperature is kept for 3 hours, and then cooled to room temperature to obtain Ta 0.5 Zr 0.5 C solid solution ceramic powder. After ball milling at 280r / min for 9h, Ta 0.5 Zr 0.5 C solid solution ceramic fine powder.

[0085] (4) Slurry impregnation: Prepare a solid solution ceramic slurry with a solid content of 10%. Take 40 g of the Ta prepared in step (3) 0.5 Zr 0.5 C solid solution ceramic powder, add 34.06g of ionized water, according to Ta 0.5 Zr 0.5 1.6 g of polyethyleneimine was added to 0.4% of the mass of C solid solution ceramic fine powder, stirred evenly, and ball milled at a speed of 180 r / min for 3 h to obtain solid solution ceramic slurry. The solid solution ceramic slurry was fully impregnated into the C / C composite porous body, and then placed in an oven at 100 ° C for 48 h to obtain C / C-Ta 0.5 Zr 0.5 C carbon / ceramic matrix.

[0086] (5) Precursor impregnation cracking and densification: A precursor solution is prepared according to a mass ratio of polycarbosilane: n-hexane = 1:3, and the C / C-Ta obtained in step (4) is fully impregnated in a high-pressure reactor at room temperature. 0.5 Zr 0.5 After drying, the C substrate was placed in a vacuum sintering furnace in a vacuum environment below 2.0 Pa and heated to 1600°C at a rate of 15°C / min for 3 hours. The above process was repeated 14 times to obtain a dense C / C-Ta 0.5 Zr 0.5 C-SiC composite material.

[0087] The C / C-Ta obtained in this example 0.5 Zr 0.5 The mechanical properties of C-SiC composite materials were tested by three-point bending and single-edge notched beam bending tests. The test results showed that its flexural strength was 185.73MPa and its fracture toughness was 13.59MPa·m 1 / 2 The flexural strength of the composite material is increased by 23.82% compared with that of the C / C composite material. 6 W / m 2 Under high heat flux density oxyacetylene flame ablation conditions, the test showed that the mass ablation rate in 120s was 1.86mg / s and the line ablation rate was 7.59μm / s.

[0088] Comparative Example 1

[0089] The other conditions were the same as those in Example 1, except that the polyethylene glycol forming agent and the polyethyleneimine dispersant were not added in step (1), which resulted in a serious phase separation phenomenon in the obtained solid solution powder, generating TaC impurities, and failing to obtain a relatively pure Ta 0.5 Zr 0.5 C solid solution powder. Ceramic powder containing impurity phase XRD Figure 4 , as shown in 5.

[0090] Comparative Example 2

[0091] The other conditions were the same as those in Example 1, except that the dispersant added in step (4) was sodium polyacrylate. As a result, a stable, fluid, and low-viscosity solid solution ceramic slurry could not be obtained, and the ceramic components could not be introduced into the C / C matrix, and C / C-Ta could not be prepared. 0.5 Zr 0.5 C carbon / ceramic matrix.

[0092] Comparative Example 3

[0093] The other conditions were the same as those in Example 1, except that the ball milling time in step (3) was set to 2 h or 12 h. The particle size of the powder after ball milling was not within the range of 0.3 to 0.8 μm. As a result, a stable solid solution ceramic slurry with good fluidity and low viscosity could not be obtained, and the ceramic component could not be introduced into the C / C matrix, and C / C-Ta could not be prepared. 0.5 Zr 0.5 C carbon / ceramic matrix.

[0094] Comparative Example 4

[0095] Other conditions were the same as those in Example 1, except that the solid content in step (4) was set to 30%. Too high a solid content would result in the dispersant not being able to fully function, and as a result, a stable, fluid, and low-viscosity solid solution ceramic slurry could not be obtained, and the ceramic components could not be introduced into the C / C matrix, and C / C-Ta could not be prepared. 0.5 Zr 0.5 C carbon / ceramic matrix.

Claims

1. A C / C-Ta 0.5 Zr 0.5 The method for preparing a C-SiC composite material is characterized by: Will Ta 0.5 Zr 0.5 Ta C solid solution ceramic powder ball milling 0.5 Zr 0.5 C solid solution ceramic fine powder, Ta 0.5 Zr 0.5 C solid solution ceramic fine powder, water and polyethyleneimine solution are mixed to obtain solid solution ceramic slurry, and the C / C composite porous body is impregnated in the solid solution ceramic slurry. After drying, a carbon / ceramic matrix is ​​obtained, and then polycarbosilane is used as a ceramic precursor to densify the carbon / ceramic matrix by impregnation and cracking of the precursor to obtain C / C-Ta 0.5 Zr 0.5 C-SiC composites; The 0.5 Zr 0.5 The preparation method of C solid solution ceramic powder is as follows: ZrO2 powder, Ta2O5 powder and carbon black powder are mixed to obtain mixed powder, and then ethanol, polyethylene glycol and polyethyleneimine solution are added to the mixed powder to obtain a mixed solution, the mixed solution is ball-milled to obtain ball-milled slurry, the ball-milled slurry is dried and pressed to obtain a ceramic body, and the ceramic body is calcined to obtain Ta 0.5 Zr 0.5 C solid solution ceramic powder; In the mixed solution, the solid-liquid mass volume ratio of polyethylene glycol to mixed powder is 1 g: 4.8~6.3 cm 3 ; In the mixed solution, the mass ratio of ethanol to polyethylene glycol is 5-7:1; In the polyethyleneimine solution, the mass concentration of polyethyleneimine is 10% to 20%, and the average molecular weight is 10000 to 20000; The mass ratio of the polyethyleneimine solution to the mixed powder is 1:6.3-7.3; The mixed solution is ball-milled to obtain a ball-milled slurry, wherein the rotation speed of the ball mill is 140-160 r / min, and the ball milling time is 6-9 h; The calcination temperature is 1900-2000°C, the holding time is 1-3h, and the heating rate is 10-15°C / min; Will Ta 0.5 Zr 0.5 C solid solution ceramic powder was ball milled at a speed of 260-280 r / min for 6-9 h to obtain Ta 0.5 Zr 0.5 C solid solution ceramic fine powder, the Ta 0.5 Zr 0.5 The particle size of C solid solution ceramic fine powder is 0.3~0.8μm.

2. A C / C-Ta according to claim 1 0.5 Zr 0.5 The method for preparing a C-SiC composite material is characterized by: In the solid solution ceramic slurry, Ta 0.5 Zr 0.5 The volume fraction of C solid solution ceramic fine powder is 10%~20%; The amount of polyethyleneimine solution added is Ta 0.5 Zr 0.5 C solid solution ceramic fine powder mass 0.4%~0.8%; Will Ta 0.5 Zr 0.5 The C solid solution ceramic fine powder, water and polyethyleneimine solution are mixed by ball milling, the rotation speed of the ball mill is 160-180 r / min, and the ball milling time is 1-3 h.

3. A C / C-Ta according to claim 1 0.5 Zr 0.5 The method for preparing a C-SiC composite material is characterized by: The C / C composite porous blank is obtained by chemical vapor deposition densification of a carbon fiber preform, wherein the carbon fiber preform is a polyacrylonitrile carbon fiber with a 2.5D needle-punched structure, and the density of the carbon fiber preform is 0.4-0.5 g / cm 3 The density of the C / C composite porous body is 0.7-0.8 g / cm 3 , porosity is 50% ~ 58%; The C / C composite porous body is immersed in a solid solution ceramic slurry and dried at 80-100° C. for 24-36 hours to obtain a carbon / ceramic matrix.

4. A C / C-Ta according to claim 1 0.5 Zr 0.5 The method for preparing a C-SiC composite material is characterized by: The process of densification of carbon / ceramic matrix by precursor impregnation and cracking is as follows: the carbon / ceramic matrix is ​​impregnated in the precursor solution, dried after impregnation, cracked after drying, and the impregnation-cracking is repeated 10 to 14 times to obtain C / C-Ta. 0.5 Zr 0.5 C-SiC composites; The precursor solution consists of polycarbosilane and n-hexane, and the mass ratio of polycarbosilane to n-hexane is 1:1-3; the cracking temperature is 1400-1600°C, the insulation time is 1-3h, and the heating rate is 10-15°C / min.

5. A C / C-Ta according to claim 1 0.5 Zr 0.5 The method for preparing a C-SiC composite material is characterized by: The particle size of the ZrO2 powder is 0.5-1.5 μm, the particle size of the Ta2O5 powder is 0.5-1.5 μm, and the particle size of the carbon black powder is 0.1-0.3 μm; In the mixed powder, the molar ratio of ZrO2 powder:Ta2O5 powder:carbon black is 2:1:13-15.

6. A C / C-Ta according to claim 1 0.5 Zr 0.5 The method for preparing a C-SiC composite material is characterized by: The ball-milled slurry is dried at 80-100° C. for 24-36 h to obtain a mixed material.

7. C / C-Ta prepared by the preparation method according to any one of claims 1 to 6 0.5 Zr 0.5 C-SiC composite materials.

Citation Information

Patent Citations

  • Multi-carbide solid solution toughened TiB2 ceramic and preparation method thereof

    CN107056314A

  • Method for preparing stable carbide solid solution ceramic based on non-contact flash-sintering technology

    CN109721362A

  • The method for preparing high-entropy oxide ceramic material is simple and low in consumption

    CN112723862A